1996
DOI: 10.1097/00007890-199606270-00002
|View full text |Cite
|
Sign up to set email alerts
|

Local Inflammatory Response Around Diffusion Chambers Containing Xenografts

Abstract: Immunoisolation of xenogeneic pancreatic islets within membrane-bound devices has been proposed as an approach to cure diabetes. We examined the local response to implanted xenografts and allografts in comparison with isografts in diffusion chambers with 0.4-microm pore membranes when implanted into epididymal fat pads of rats. These membranes prevented host cell entry into the device but did not prevent passage of large molecules such as IgG and IgM. Well-differentiated allogeneic tissues (Sprague-Dawley rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 13 publications
2
33
0
Order By: Relevance
“…The βAir device would tentatively benefit from increasing its surface‐to‐volume ratio; however, with the limitations that the device will still have to keep dimensions reasonable for clinical application. Notably, a membrane with pore sizes as large as 0.45 μm seems able to control islet allograft rejection in rodent models,5, 18, 19 as well as in this and a previous clinical trial,20 ie, preventing cell‐to‐cell contact between donor and recipient cells seems sufficient to prevent HLA immunization and allograft rejection. Implantation of the islets in an alginate gel potentially also impairs diffusion.…”
Section: Discussionsupporting
confidence: 61%
“…The βAir device would tentatively benefit from increasing its surface‐to‐volume ratio; however, with the limitations that the device will still have to keep dimensions reasonable for clinical application. Notably, a membrane with pore sizes as large as 0.45 μm seems able to control islet allograft rejection in rodent models,5, 18, 19 as well as in this and a previous clinical trial,20 ie, preventing cell‐to‐cell contact between donor and recipient cells seems sufficient to prevent HLA immunization and allograft rejection. Implantation of the islets in an alginate gel potentially also impairs diffusion.…”
Section: Discussionsupporting
confidence: 61%
“…is relatively easy to perform, the encapsulated tissue is easily implanted by syringes, and the method yields excellent surface/volume ratios for transport kinetics. Experiments in immunoisolation have demonstrated that encapsulated syngeneic cells implanted into rodents do quite well, but encapsulated allogeneic cells have a short survival period, and xenografts are destroyed even faster (Brauker et al 1996;Loudovaris et al 1992).…”
Section: A Competitive Analysis Of Immunoisolatory Encapsulation Techmentioning
confidence: 99%
“…At this time, the amount of insulin recovered and the kinetics have almost fully returned to normal and are not significantly different from those in the control group. This is a rather unexpected finding, since several publications report increasing fibrosis during the first months after implantation [19][20][21][22]. A possible explanation could be changes in, or even degradation of, the membrane material.…”
Section: Discussionmentioning
confidence: 72%
“…The in vivo diffusion barrier will depend partly on the immunoisolating membrane but also on the tissue reaction in the recipient. The development of an avascular foreing body reaction around an implant, a common problem in the fields of both macro-and microencapsulation, will hinder the survival and function of the encapsulated graft, while a well-vascularized surrounding tissue should be favorable [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%